Instituto de Educação do Amapá: uma história de educação pelo exemplo - Carvalho, João Wilson Savino (2012)
The objective of this work is to construct a history of the Amapa Institute of Education (IETA), a school for training teachers in the high school level, created in Macapa (AP) in 1949 without proper operating condition, but was gradually acquiring an image of quality public school and enormous prestige among the community of Amapá, until its dissolution in 2005, claiming the restrictions of LDBEN training of teachers in the high school level and the need for physical space to implement State University. The chosen methodology was historical research, qualitative, of literature (texts, articles and books on the IETA), documentary (basic documents and pictures IETA) and field (memoir tells of local), having as epistemological materialism dialectical, methodological foundation in the thought of Justino de Magalhães, Paolo Nosella and Esther Buffa, as the application of the dialectical method of research the history of educational institutions, and Maria Cecilia Minayo, for whom dialectics is a way of thought and research craft an intellectual. The common thread of research are the representations of work and knowledge of the teacher teaching the early grades in school culture of IETA, the way in which they appear in the speech of the actors of the educational practice every day in the curriculum, the distribution of physical space and the architectural designs of the building. In the data collection techniques were used in the methodology inspired by Carlos Ginzbourg. The working hypothesis of the thesis provides the title, because education by example is understood as the representation of instituting educational practice throughout the history of the IETA thus a constant along the trajectory of the school. Thus, the history of the Institute of Education is designed in five phases: pioneer (representations by certain teacher s janarismo New State), consolidation (firm to the representation of education for example), height (maximum of IETA\'s prestige in the community Amapá); crisis and extinction.